Risk and protective factors associated with mental health among female military veterans: results from the veterans' health study - Richard E. Adams; Yirui Hu; Charles R. Figley; Thomas G. Urosevich; Stuart N. Hoffman; H. Lester Kirchner; Ryan J. Dugan; Joseph J. Boscarino; Carrie A. Withey; Joseph A. Boscarino (BMC, 2021)
Abstract Background This study focuses on factors that may disproportionately affect female veterans' mental health, compared to men, and is part of a larger study assessing the prevalence of mental health disorders and treatment seeking among formerly deployed US military service members. Methods We surveyed a random sample of 1,730 veterans who were patients in a large non-VA hospital system in the US. Based on previous research, women were hypothesized to be at higher risk for psychological problems. We adjusted our results for confounding factors, including history of trauma, childhood abuse, combat exposure, deployments, stressful life events, alcohol misuse, psychological resources, and social support. Results Among the veterans studied, 5% were female (n = 85), 96% were White (n = 1,161), 22.9% were Iraq/Afghanistan veterans (n = 398), and the mean age was 59 years old (SD = 12). Compared to males, female veterans were younger, unmarried, college graduates, had less combat exposure, but were more likely to have lifetime PTSD (29% vs. 12%.), depression (46% vs. 21%), suicidal ideation (27% vs. 11%), and lifetime mental health service use (67% vs. 47%). Females were also more likely to have low psychological resilience and to have used psychotropic medications in the past year. Using multivariate logistic regression analyses that controlled for risk and protective factors, female veterans had greater risk for lifetime PTSD, depression, suicidal thoughts, and for lifetime use of psychological services, compared to males. Since 95% of the population in this study were male and these results may have been statistically biased, we reran our analyses using propensity score matching. Results were consistent across these analyses. Conclusion Using a sample of post-deployment veterans receiving healthcare services from a large non-VA health system, we find that female veterans are at greater risk for lifetime psychological problems, compared to male veterans. We discuss these findings and their implications for service providers.